Representasi Standar Perempuan Cantik dalam Iklan Perawatan Rambut L'oreal di Tiktok - Radika Dava Praditya; Yermanida Hayyatun Nufus; Fajar Junaedi; Farchan Jelani (Universitas Muhammadiyah Klaten, 2026)
This advertisement features a representation of straight hair as the ideal hair for women. Advertisements often promote certain beauty standards, particularly by idealizing straight hair as a characteristic of the